2008
DOI: 10.1525/sp.2008.55.2.254
|View full text |Cite
|
Sign up to set email alerts
|

"We Weren't Like No Regular Dope Fiends": Negotiating Hustler and Crackhead Identities

Abstract: We investigate how participants in the street economy of crack cocaine construct a "hustler" identity by contrasting their social behaviors and styles with a dialectically contrastive crackhead identity. For those who are proximate to, or involved in, the crack cocaine economy, effort is required to avoid being labeled a crackhead. Would-be hustlers construct boundaries that separate them from others on the street through talk and behavior. We draw on interviews conducted with 28 men convicted of committing vi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
83
0
1

Year Published

2013
2013
2024
2024

Publication Types

Select...
6
3

Relationship

1
8

Authors

Journals

citations
Cited by 100 publications
(84 citation statements)
references
References 26 publications
0
83
0
1
Order By: Relevance
“…Ugelvik, 2014), may to some extent account for the less reference made to issues of addiction and dependency in the conversations and interviews with prisoners on topic of drug use in prison. Previous research has shown that individuals categorised as ''junkies'' and ''crack heads'' hold a particularly low status in prisons, because their addiction testifies weakness and a lack of control (Copes, Hochstetler, & Williams, 2008;Ugelvik, 2014). In such a normative environment, prisoners would perhaps be somewhat more reluctant to emphasise addiction and dependency as explanations for their drug use.…”
Section: Discussionmentioning
confidence: 99%
“…Ugelvik, 2014), may to some extent account for the less reference made to issues of addiction and dependency in the conversations and interviews with prisoners on topic of drug use in prison. Previous research has shown that individuals categorised as ''junkies'' and ''crack heads'' hold a particularly low status in prisons, because their addiction testifies weakness and a lack of control (Copes, Hochstetler, & Williams, 2008;Ugelvik, 2014). In such a normative environment, prisoners would perhaps be somewhat more reluctant to emphasise addiction and dependency as explanations for their drug use.…”
Section: Discussionmentioning
confidence: 99%
“…We argue that young adolescents largely approached questions of alcohol socially and relationally. They applied well-established social categories and engaged in symbolic boundary work against groups in close social proximity to appear as functional and mature (Copes, Hochstetler & Williams 2008). In particular, the dichotomy of adolescents versus adults was central in young adolescents' perceptions of drinking.…”
Section: Discussionmentioning
confidence: 99%
“…Such distinctions are especially common among drug users (Copes, Hochstetler, and Williams 2008;Copes et al 2014). While there are subtle differences depending on the drug in question and the characteristics of users, the general distinction that drug users make is between those who are functional and those who are dysfunctional.…”
Section: Discussionmentioning
confidence: 99%
“…Users can also draw on subcultural values. For example, crack users may claim they are not crackheads by referencing their ability to live by the code of the street, specifically the value of having courage and defending themselves from others (Copes et al 2008). The college students we interviewed drew from stories about hard work, academic success, and the benefits of moderation prevalent among those in the middle-class.…”
Section: Discussionmentioning
confidence: 99%